2020
DOI: 10.1038/s41467-020-17178-5
|View full text |Cite
|
Sign up to set email alerts
|

Blood genome expression profiles in infants with congenital cytomegalovirus infection

Abstract: Congenital CMV infection (cCMVi) affects 0.5-1% of all live births worldwide, making it the leading cause of sensorineural hearing loss (SNHL) in childhood. The majority of infants with cCMVi have normal hearing at birth, but are at risk of developing late-onset SNHL. Currently, we lack reliable biomarkers to predict the development of SNHL in these infants. Here, we evaluate blood transcriptional profiles in 80 infants with cCMVi (49 symptomatic, 31 asymptomatic), enrolled in the first 3 weeks of life, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…The complexity of this infection is perhaps best illustrated by a recent report describing different phenotypes of monozygotic twins with cCMV infections of which most were monochorionic [ 29 ]. Furthermore, recent findings from a transcriptomic study of infants with symptomatic and asymptomatic cCMV infections failed to define a pattern of gene expression that could distinguish these two clinical phenotypes, although it should be noted that this study cataloged transcriptomic patterns in peripheral blood cells and not in cells from target tissues such as the CNS [ 30 ]. Together, these data suggest that the CNS sequelae associated with cCMV infection likely represent a continuum and cannot be represented by a simple binary clinical classification of symptomatic and asymptomatic cCMV infection.…”
Section: Central Nervous System Disease Following Congenital Hcmv Infectionsmentioning
confidence: 99%
“…The complexity of this infection is perhaps best illustrated by a recent report describing different phenotypes of monozygotic twins with cCMV infections of which most were monochorionic [ 29 ]. Furthermore, recent findings from a transcriptomic study of infants with symptomatic and asymptomatic cCMV infections failed to define a pattern of gene expression that could distinguish these two clinical phenotypes, although it should be noted that this study cataloged transcriptomic patterns in peripheral blood cells and not in cells from target tissues such as the CNS [ 30 ]. Together, these data suggest that the CNS sequelae associated with cCMV infection likely represent a continuum and cannot be represented by a simple binary clinical classification of symptomatic and asymptomatic cCMV infection.…”
Section: Central Nervous System Disease Following Congenital Hcmv Infectionsmentioning
confidence: 99%
“…A wide range of molecular and cellular profiling assays are currently available for the study of the human immune response [9]. Of all the omics technologies available, transcriptomic approaches are the most scalable, have the most breadth and robustness, and therefore appear to be best suited for the study of infectious diseases in children and adults [5 ▪▪ ,10–13]. The transcriptome represents the complement of RNAs (messenger-m-RNA) that are transcribed from the genome.…”
Section: Host Transcriptional Signatures For the Diagnosis Of Infecti...mentioning
confidence: 99%
“…In the quest for biomarkers of SNHL, a small study analysed host transcriptional profiling from blood spots in children with congenital CMV, and identified a preliminary signature that was associated with long term sequelae [40]. A subsequent larger study analysed the whole blood transcriptome in neonates with symptomatic and asymptomatic cCMV infection [5 ▪▪ ]. Unexpectedly, the study showed that the biosignatures of infants with symptomatic and asymptomatic cCMV disease were similar.…”
Section: Congenital and Perinatal Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue is quite challenging since current recommendations stipulate that all infants with cCMV infection must undergo periodic hearing surveillance testing for years. Recently, Ouellette et al identified a 16-gene classifier signature associated with the development of SNHL with 92% accuracy in 80 infants with cCMV infection. These promising results are the impetus for an upcoming National Institutes of Health–funded observational trial to evaluate blood transcriptional profiles as a potential biomarker for SNHL (DMID 21-0034).…”
mentioning
confidence: 99%